Yield of passion fruit under different irrigation levels and potassium doses by fertirrigation - Sousa, Valdemício Ferreira de; Folegatti, Marcos Vinícius; Frizzone, José Antônio; Corrêa, Rodrigo Alessandro de Lima; Eloi, Waleska Martins (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to study the effect of four irrigation levels and five K doses applied through fertirrigation by drip irrigation system in the yellow passion fruit (Passiflora edulis Sims f. flavicarpa Deg.) yield. A complete randomized block design in plot subdivided with four replications was used. The treatments resulted from the combination of four irrigation levels [0.25V (926.76 L), 0.50V (1,528.20 L), 0.75V (2,117.28 L) and 1.00V (2,706.36 L), where V is the average volume of water applied in lysimeter with passion fruit plant] with five K doses (0.000, 0.225, 0.450, 0.675 and 0.900 kg plant-1 year-1 of K2O). The commercial yield was affected by irrigation levels, K doses and by the interaction irrigation levels vs. K doses. The majors values of passion fruit commercial yield were obtained with the application of 0.450 to 0.675 kg plant-1 year-1 of K2O, and water levels of 1,528.20 to 2,117.28 L plant-1 year-1, respectively.